Adipocinas, excreção urinária de albumina, sensibilidade insulínica e função da célula beta na deficiência isolada do hormônio de crescimento - Oliveira, Carla Raquel Pereira (2010)
The aim of this study was to assess the dissociation between the presence of cardiovascular risk factors, and the lack of premature atherosclerosis and left venticular hipertrophy (LVH) in isolated GH deficiency (IGHD) due to a mutation in the GH releasing hormone receptor gene. A two step protocol was performed. In the first experiment, serum adiponectin and leptin, and urinary albumin excretion (UAE) were studied in 20 IGHD individuals (7 M/ 13 F; 50,8 ± 14,6 years) and 22 control subjects (C) (8 M/ 14 F; 49,9 ± 11.5 years). IGHD subjects in comparison to C presents high adiponectin levels (p= 0,041) whereas leptin and UAE were similar. In the second experiment, oral glucose tolerance test (1,75 g/Kg in IGHD and 75 g in C) with glucose and insulin mesuarements at 0, 30, 60, 90, 120 e 180 minutes was performed in 24 IGHD subjects (12 M/ 12 F; 39,25 ± 11,73 years) and 25 C subjects (14 M/ 11 F; 39,96 ± 12,49 years). Insulin sensitivity (IS) was assessed by HOMAir, lower values, higher IS; QUICKI, OGIS 2 and OGIS, higher values, higher IS (for the three parameters). Beta cell function was assayed by HOMA-beta, insulinogenic index and area under the curve of the relation between insulin and glucose (AUC I/G). ANOVA indicated glucose response was higher (p<0,0001) and insulin response presented a trend of reduction (p=0,08) in the IGHD gruop. The number of pacients with glucose intolerance was higher (p= 0,001) in the IGHD group. HOMAir was lower (p= 0,041), QUICKI and OGIS 2 showed a trend of elevation (p= 0,066 and p= 0,09, respectively) in the IGHD subjects, whereas OGIS 3 showed no difference between both groups. IGDH presented reduction in HOMA-beta (p= 0,015), insulinogenic index (p<0,0001) and AUC I/G (p=0,02). These different adipokine profile with high adiponectin and normal leptin levels, linked to normal insulin sentitivity may delay vascular damage, LVH and lesions of the renal endothelium (normal UAE). Normal IS and reduced beta cell function featured this IGDH model.